A MULTICENTRE, RETROSPECTIVE STUDY OF EPIDEMIOLOGY AND OUTCOME OF APLASTIC ANAEMIA AMONG ADULT POPULATION IN SABAH AND SARAWAK FROM YEAR 2006 TO 2017 - Grace Wan Chieng, Lee; Mei Yee, Yeap; Xin Yee, Tan; Andy Sing Ong, Tang; Yoke Fun, Ho; Kian Boon, Law; Shalin Lee, Wan Fei; Lee Ping, Chew; Lily Lee Lee, Wong (Malaysian Medical Association, 2024)
Introduction: Aplastic anaemia (AA) is a rare disorder of bone marrow failure, characterized by bone marrow hypocellularity with pancytopenia. The annual incidence rates of AA in Asia are observed to be two to three times higher than Europe and North America. Since the introduction of immunosuppressive therapy (IST) and of allogenic stem cell transplant (SCT), the outcome of severe AA has significantly improved. We conducted a 12-year multi-centre retrospective study among the adult AA population in Sabah and Sarawak. Materials and methods: A total of 119 AA patients had been identified from hospital records of the involved sites, namely Queen Elizabeth Hospital in Sabah, Sarawak General Hospital, Sibu Hospital, Miri Hospital and Bintulu Hospital in Sarawak from Jan 2006 to Dec 2017. Results: The median age at diagnosis was 46 years, and native ethnic group from Sabah, Kadazan-Dusun, recorded the highest percentage of 41.2%, which could be explained by higher frequency of HLA-DRB1*15:01, an alelle linked to increased risk of AA, among this ethnic group. The majority of patients (59.7%) received cyclosporine (CsA) as monotherapy or in combination with other non-IST agents such as danazol, which was instituted in 52.1% of the patients, while a third of them (33.7%) received antithymocyte globulin (ATG) therapy with or without CsA, and 12.4% underwent allogenic SCT. The five-year overall survival (OS) for all AA patients was 76.1%. Elderly patients >60 years old and those with severe disease had more inferior 5-year survival. Conclusion: A prospective study is warranted to determine the true incidence rate, epidemiological distributions, treatment outcome and overall survival of AA patients in Malaysia. Establishment of allogenic SCT in East Malaysia is imperative to make this curative therapy more accessible to patients with severe disease and improve the outcome.